Pelatihan Penggunaan Aplikasi Belajar Daring Google Classroom Dan Zoom Meeting Bagi Anak Usia Sekolah Di Desa Huta Padang - hasibuan, erwina azizah; wendi, al (Jurnal Pengabdian Masyarakat, 2021)
The Covid-19 pandemic requires the teaching and learning process to be carried out from home, by utilizing classroom learning media and zoom meetings. The purpose of the online learning training activities of google classroom and and zoom meetings for school-age children in the village of Huta Padang is to provide teachers with an understanding of how to conduct and develop online learning so that they can do learning from home. The importance of this online learning training is to prepare teachers and schools in the online learning process to run properly. The steps taken in this training are first, implementing the Health protocol before and after implementing the training. Second, introducing online learning to students. Third, explain about Google Classroom and how to use it. And the fourth practice of using google classroom. From the implementation of the activities carried out, it was found that the training participants could understand the training material well and develop online learning in Google Classroom.